Investigation of Thermal Management System of a Lithium-Ion Battery in Electric Vehicle. (2022) - Prajapati, Shivam; Upadhyay, Yogesh; Kumar, Yogesh; Kumar Singh, Manish
Abstract: The performance of any Electric vehicle depends upon the Power Battery used in the vehicle. Both very high as well as low temperatures can have a negative impact on the efficiency of the battery. Operation of a battery at a high temperature may lead to overheating or even lead to an explosion of the battery which has been witnessed in lots of cases. If a battery operates at a lower temperature then also it might be complicated for the batteries to work efficiently, So this paper focuses on the Thermal management system of Lithium-ion batteries. There are different methods and ways studied by previous researchers by which rise in the temperature in the batteries could be balanced. A phase change material (PCM) having properties of copper foam/paraffin was used in the battery pack to get the optimum temperature for the battery module. Phase change materials have a lower value of thermal conductivity so in this study copper foam was used which has a better thermal conductivity value i.e 0.21 W/m-K. Solidus and liquidus temperature also play a major role in determining the temperature rise. The rise in temperature in the battery module depends on how the cell inside the modules is arranged. It also depends on the shape and size of the cells used. This paper focuses on getting the most accurate arrangement of the cells to get the most efficient battery module.